2002
DOI: 10.1016/s0006-2952(02)01218-2
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate antagonists limit tumor growth

Abstract: Neuronal progenitors and tumor cells possess propensity to proliferate and to migrate. Glutamate regulates proliferation and migration of neurons during development, but it is not known whether it influences proliferation and migration of tumor cells. We demonstrate that glutamate antagonists inhibit proliferation of human tumor cells. Colon adenocarcinoma, astrocytoma, and breast and lung carcinoma cells were most sensitive to the antiproliferative effect of the N-methyl-D-aspartate antagonist dizocilpine, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
97
0
14

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 42 publications
3
97
0
14
Order By: Relevance
“…An assessment of the direct action of glutamate on cancer cell growth was first reported in the 1950s, although no change in growth was found [48]. Inhibition of NMDA receptors was subsequently demonstrated to inhibit cell growth in a variety of cancer cell lines in standard media conditions [49][50][51]. Using a similar approach to the current study, Abdul and Hoosein [49] reported a moderate decrease in growth with the uncompetitive NMDA antagonist memantine in two of the cell lines that we have tested.…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of the direct action of glutamate on cancer cell growth was first reported in the 1950s, although no change in growth was found [48]. Inhibition of NMDA receptors was subsequently demonstrated to inhibit cell growth in a variety of cancer cell lines in standard media conditions [49][50][51]. Using a similar approach to the current study, Abdul and Hoosein [49] reported a moderate decrease in growth with the uncompetitive NMDA antagonist memantine in two of the cell lines that we have tested.…”
Section: Discussionmentioning
confidence: 99%
“…26,27,31,34 The goal of the current study was to evaluate the efficacy of the glutamate release inhibitor riluzole and the NMDA receptor antagonist memantine in animal models of intracranial glioma and gliosarcoma. Although it is well known that riluzole and memantine cross the blood-brain barrier and reach appropriate concentrations for the therapy of neurodegenerative disorders such as ALS and Alzheimer’s disease, therapy with systemic riluzole or memantine in our models was ineffective.…”
Section: Discusssionmentioning
confidence: 99%
“…Toxic levels of glutamate associated with high-grade gliomas have been demonstrated both in vitro and in vivo. 4,27 Protection of the peritumoral functional, but possibly infiltrated, brain may indeed be beneficial for multiple reasons. Glutamate-mediated excitotoxicity to peritumoral astrocytes as well as neurons may contribute to decreased patient function due to the facilitation of peritumoral edema, direct cellular toxicity, and seizure activity.…”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports showed that glutamate receptor antagonists inhibit cell proliferation of colon cancer, breast cancer, and lung cancer, and that the antiproliferative effect of the glutamate receptor antagonists is ascribed to their suppressive effect on cell division concomitant with an increase in cell death [9-11]. Nevertheless, due to their poor efficacy in penetrating the BBB, the glutamate receptor antagonists have had limited success in clinical applications to brain tumors [10]. …”
Section: Introductionmentioning
confidence: 99%